Global Value Chain Development Report 2017 : Measuring and Analyzing the Impact of GVCs on Economic Development - World Bank Group; IDE-JETRO; OECD; UIBE; World Trade Organization (Washington, DC: World Bank, 2018)
Global value chains (GVCs) break up the production process so at different steps can be carried out in different countries. Today’s official statistical information systems, designed to measure economic activity in a pre-GVC world, have struggled to keep pace with these changes. Conventional measures of trade, important though they remain, measure the gross value of transactions between partners and so are not able to reveal how foreign producers, upstream in the value chain, are connected to final consumers at the end of the value chain. The importance of the GVC phenomenon has stimulated researchers to develop statistics and analysis based on the value added in trade. The GVC phenomenon also demands that researchers analyze the discrete tasks or phases in the production process. This first GVC development report draws on the expanding research that uses data on the value added in trade. Its main objective is to reveal the changing nature of international trade that can be seen only by analyzing it in terms of value added and value chains. This report highlights how shifting the analysis to value added radically changes the picture.